PT PERTAMINA'S CORPORATE COMMUNICATION STRATEGY IN RESPONSE TO THE MINISTER OF FINANCE'S INSINUATION OVER THE STAGNATION OF NEW REFINERY CONSTRUCTION - Ketut Deta Rastika (Jurnal Media Akademik (JMA), 2025)
This study aims to analyze PT Pertamina's corporate communication strategy in response to the insinuation of the Minister of Finance of the Republic of Indonesia regarding the slow construction of new refineries that are part of the Refinery Development Master Plan (RDMP) and Grass Root Refinery (GRR) projects. This research uses a descriptive qualitative approach with a case study method, through analysis of the company's official statements, national media reports, and digital communication activities on various official Pertamina platforms. The results show that Pertamina implements a defensive-reflective communication strategy that emphasizes data-based clarification without being confrontational, and uses a framing strategy to shift public perception from criticism to understanding the complexity of national energy policies. In addition, Pertamina applies the principles of transparency and reassurance through regular publication of project progress, as well as strengthening relations with the media as an instrument to control public opinion (media relations). The communication built is diplomatic and synergistic with the government, reflecting the application of the principles of Stakeholder Theory and Image Repair Theory in the management of SOEs' reputations. Overall, Pertamina's communication strategy has proven effective in maintaining the stability of the company's image, stabilizing public opinion, and strengthening institutional legitimacy amid political pressure and public expectations.